Analysis of Weaknesses in Playing Techniques of The Indonesian Women's National Volleyball Team in The 2020 Tokyo Olympic Qualifications - Lisviana, Grace Ayuda; Sulistyarto, Soni (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This study aims to analyze the weaknesses in the playing techniques of the Indonesian women's national volleyball team during the 2020 Olympic qualifications. The method used is descriptive quantitative by analyzing video footage of the match between Indonesia and South Korea. Data were analyzed using percentage techniques based on the success and failure of playing techniques. The results revealed that Indonesia's defeat was caused by weaknesses in several playing techniques, namely receive (68%), dig (54%), spike (54%), serve (43%), toss (41%), and block (22%). These weaknesses affected the team's performance, resulting in Indonesia finishing third in Group B after losing to South Korea and Kazakhstan (0-3). In conclusion, the Indonesian national team needs to improve their playing techniques through thorough evaluation and intensive training. To compete at the international level and defeat strong teams like South Korea, players and coaching staff must collaborate to enhance the team's performance in the future